Pengaruh Work Family Conflict Terhadap Stres Kerja Pada Working Mom Sebagai Tenaga Kerja Formal Di Kabupaten Karawang - Fortuna, Azahra Ananda; Mora, Linda; Tyas, Devi Marganing (Gorontalo Management Research, 2025)
Working moms as formal workers in Karawang Regency are the focus of this study, which has a target to measure work family conflict on work stress. This study aims to determine and analyze the effect of work family conflict on work stress in working moms. This research method uses a quantitative method, participants in this study were 151 respondents. The analysis used in this study is a simple regression analysis using SPSS 25 software. The results of the study showed that there was a significant influence between work family conflict and work stress in working moms.